(untitled) (International Journal of Engineering and Computer Science, 2016)
India is the country in which most of the people are depend on the agriculture, According to the survey of Government of India Agriculture plays a vital role in the Indian economy. Over 70 per cent of the rural households depend on agriculture as their principal means of livelihood. India ranked in the world’s five largest producers of over 80% of agricultural produce items, including many cash crops such as coffee and cotton, in 2010. It has become one of the world’s largest suppliers of rice, cotton. Cotton is very important crop in our country and if some disease will affected on that crop the total economy of the farmer as well as country will get collapse. Normally in my country if disease will get detected by the farmer he will contact to the Experienced person and get solution for the same but if the detection and identification of disease not correct will badly affecting on the plant. In second case farmer will contact to the owner of pesticide shop the person will suggest some wrong treatment with respect to his experience. Third case is that farmers are just going with nature they thing is that the disease will get cleared automatically in some period of span. The main motivation of this topic is to identify the type of disease and quantify the damage of crop thereby providing the treatment for the respective disease. This identification and detection of disease is possible by using image processing techniques on the different parts of cotton crop. This review paper will give information about the possible disease on cotton plants as well as possible treatment should provide to the farmer.